2015
DOI: 10.3389/fmicb.2015.01162
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genes that are differentially expressed during the Sclerotinia sclerotiorum–Phaseolus vulgaris interaction

Abstract: The fungus Sclerotinia sclerotiorum (Lib.) de Bary, one of the most important plant pathogens, causes white mold on a wide range of crops. Crop yield can be dramatically decreased due to this disease, depending on the plant cultivar and environmental conditions. In this study, a suppression subtractive hybridization cDNA library approach was used for the identification of pathogen and plant genes that were differentially expressed during infection of the susceptible cultivar BRS Pérola of Phaseolus vulgaris L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 60 publications
4
41
1
Order By: Relevance
“…Although the aspS gene was not up-regulated in the current study, genes encoding proteases similar to aspS (SS1G_05329 and SS1G_02870), were up-regulated at the very early stages of the infection in support of the previous studies. However, a gene encoding another aspartyl protease , SS1G_03181, was also detected in the S. sclerotiorum – P. vulgaris interaction with increased expression at the spreading necrosis stage [40]. SS1G_03181 was up-regulated at 24-48 hpi in the current study which is in agreement with these earlier findings.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Although the aspS gene was not up-regulated in the current study, genes encoding proteases similar to aspS (SS1G_05329 and SS1G_02870), were up-regulated at the very early stages of the infection in support of the previous studies. However, a gene encoding another aspartyl protease , SS1G_03181, was also detected in the S. sclerotiorum – P. vulgaris interaction with increased expression at the spreading necrosis stage [40]. SS1G_03181 was up-regulated at 24-48 hpi in the current study which is in agreement with these earlier findings.…”
Section: Resultssupporting
confidence: 91%
“…They suggested that since SsPG1 expression was also induced by carbon starvation and repressed by galacturonic acid that it may be involved in both early penetration events and lesion expansion. During Phaseolus vulgaris infection, SsPG1 is induced during the later stages of the interaction (48-72 hpi), SsPG 3 is up-regulated earlier at 12 hpi, while SsPG6 exhibits a bimodal pattern with peaks of expression at 6 and 48 hpi [40]. SsPG3 and SsPG6 are also potent inducers of light-dependent necrotic reactions [54].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations